Profesionalisme Pelayanan Tenaga Kesehatan dalam Mencegah Malpraktek Medik: Professionalism of Health Services in Preventing Medical Malpractice - Ahdiana Yuni Lestari; Atik Septi Winarsih; Yaltafit Abror Jeem; Titania Isyani Ramadhani; Widya Nur Aini Baride (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The partner of this community service program is the Banguntapan II Health Center which is located in Kapanewon Banguntapan, Bantul, Regency. The problems are Health workers don’t understand the manufacture and management of medical records according to applicable regulations; Limited public understanding of medical emergencies; The limited number of puskesmas staff in relation to excellent service. Solutions of theses problems are providing counseling about the legal aspects of medical records and medical malpractice, medical emergencies from the medical aspect, as well as knowledge service at the puskesmas. The method used to carry out this series of activities is counseling related to legal aspects of medical records and medical malpractice, medical emergencies from the medical aspect, as well as knowledge of excellent service to health workers of Banguntapan II Health Center, Community Health, Center HR, and Community Leaders. The results show that before counseling was held regarding the manufacture and management of medical records and malpractice according to applicable regulations, regarding medical emergencies, and excellent service, there were still some service participants who did not understand the counseling material. After the counseling was held, all service participants understood the counseling material. Thus, the provision of counseling shows that the service participants have understood the material that has been given during the counseling, so that the participants' understanding is significantmethodology, results, and conclusions but do not need to make these words explicit.